MUSCULOSKELETAL DISORDERS PADA PEKERJA KULI PANGGUL DI PASAR PANDAN SARI KOTA BALIKPAPAN - Yuliana, Lina; Zulfikar, Iwan; Yumna Faiq, Muhammad (Program Studi Kesehatan dan Keselamatan Kerja, 2022)
Based on direct observations made at Pandan Sari Market lifting weights without tools and lifting loads exceeding the threshold value, it is necessary to write this paper to help educate the dangers of Musculoskeletal Disorders (MSDs) as a Work Safety Program in the form of control. This study aims to determine the level of risk of musculoskeletal complaints in manual lifting activities using the Nordic Body Map (NBM) method and to determine the level of risk of work posture on musculoskeletal complaints to workers using the Rapid Entire Body Assessment (REBA) method. The author uses the NBM questionnaire for cases of Musculoskeletal Disorders (MSDs) complaints against workers and uses the Rapid Entire Body Assessment (REBA) method to assess body posture at work. The results of the discussion show that there is a discrepancy in the level of risk of high work posture and low level of risk of MSDs, although the results of the level of risk of MSDs are low, workers experience MSDs. Based on the REBA method, the risk level of the work posture is predominantly high, which means immediate action is needed and the Nordic Body Map (NBM) method test, it is concluded that the risk level for MSDs complaints is at a moderate risk level, which means that action may be needed in the future.